Reclaiming Our Universities: A Manifesto to Dismantle the UK HE Sector Neoliberal Agenda - Marian Mayer; Sue Eccles (Angles)
This article is a response to the introduction of the Higher Education and Research Act (HERA) 2017, which in effect opens the door to privatised, deregulated Higher Education (HE) across the UK. The Act allows private for-profit companies, from their inception, to use the university title (previous legislation required a waiting period of four years), award degrees, and charge unregulated fees: they will not be required to establish or fund student unions. This is, we argue, the neoliberal project in action. As publicly-funded universities in the UK struggle to meet politically-driven imperatives such as the Research Excellence Framework, the Teaching Excellence Framework, audits, metrics and other performance indicators, new for-profit funded universities are emerging which position themselves as meeting industry and student expectations, rather than as centres for the creation, dissemination and research of knowledge. The only challenges to the hegemony of Universities UK (UUK), regulation of universities, and the governing bodies of pre-92 universities have come from individual academics and students, via UCU industrial action in defence of academic staff pensions. Strikes in 61 UK universities in 2018 were widely seen as a watershed in HE activism. Against this backdrop, an ideologically-driven, neoliberal agenda has begun to dismantle publicly-funded HE in England and Wales. To demonstrate this, we develop an interactive model predicated on the DNA double helix, where we illustrate links between government Acts and regulations and the concomitant dismantling of public sector education. Based on the review of over 140 government instruments, we argue the model represents the backbone of the neoliberal project which is intended to privatise all areas of education in the UK. To challenge this neoliberal agenda, we propose a manifesto to reclaim HE in England and Wales. Whilst in part the manifesto is based on the premise that a Labour government will be elected within the next 5 years, this is not a prerequisite for reclaiming our universities. The manifesto seeks to establish University Community Cooperatives — collegiate, collaborative spaces of knowledge creation. Our analysis of the current political landscape in England and Wales, in light of recent activism within HE, leads us to be optimistic. We argue that it is possible, through the efforts of individuals, collectives, unions and all citizens concerned with, and in, HE to work together to achieve truly inclusive, democratic, communities of learning. These communities will reclaim universities, organise, and act for the benefit of civic society. Staff and student unions have come together in common cause to challenge the neoliberal university model, rendering them the power to dismantle the neoliberal agenda; our manifesto seeks to contribute to the struggle to reject neoliberal realism and reclaim our universities.